Patterns of antiretroviral therapy adherence and impact on HIV RNA among patients in North America. - Genberg, Becky L; Wilson, Ira B; Bangsberg, David R; Arnsten, Julia; Goggin, Kathy; Remien, Robert H; Simoni, Jane; Gross, Robert; Reynolds, Nancy; Rosen, Marc; Liu, Hong Hu (AIDS (London, England), 2012)
Adherence to antiretroviral therapies (ART) is the strongest predictor of viral suppression among individuals infected with HIV, however, limited data exists to understand the patterns of adherence that confer the greatest benefit across different ART regimens.
Keywords: Acquired Immunodeficiency Syndrome; Adult; Anti-HIV Agents; Drug Monitoring; Female; Humans; Logistic Models; Longitudinal Studies; Male; Medication Adherence; Middle Aged; North America; RNA, Viral; Treatment Outcome